THE RELATIONSHIP BETWEEN GROWTH AND VOLATILITY IN SMALL FIRMS. Issue 8 (20th August 2014) - Moreno, Ana Maria; Zarrias, Jose A; Barbero, Jose L.
Abstract : Purpose: This paper investigates the effect of predictors of growth (entrepreneurial orientation and environmental hostility) and growth itself on small firm volatility. The objective is to find out a) Whether growth and volatility possess a similar nature b) What are the predictors of small firm volatility. Design/methodology/approach: Questionnaire data was collected from CEOs of 433 Spanish small firms (less than 500 employees) who provided qualitative as well as quantitative information. Findings: We find that some of the predictors on growth can also be used to predict firm volatility. Specifically, we find that firm volatility is influenced by entrepreneurial orientation and environmental hostility. Growth also influences firm volatility. We also find a strong interaction effect of growth and firm size on firm volatility. We conclude that although growth and firm volatility are related concepts, they are different. Originality/value: Growth has concentrated small firm research during the last twenty years. However, during the last few years, the environment has become very dynamic and small firms need research helping them to deal with such dynamism. There are few studies on firm-level volatility. Our research helps understand more the determinants of small firm volatility.